Irradiation of Epithelial Carcinoma Cells Upregulates Calcium-Binding Proteins That Promote Survival under Hypoxic Conditions - Ren, Yan (2016)
Hypoxia is thought to promote tumor radio-resistance via effects on gene expression in cancer cells that modulate their metabolism, proliferation, and DNA repair pathways to enhance survival. Here we demonstrate for the first time that under hypoxic condition A431 epithelial carcinoma cells exhibit increased viability when exposed to low-dose γ-irradiation, indicating that radiotherapy can promote tumor cell survival when oxygen supply is limited. When assessed using iTRAQ quantitative proteomics and Western blotting, irradiated tumor cells were observed to significantly up-regulate the expression of calcium-binding proteins CALM1, CALU, and RCN1, suggesting important roles for these mediators in promoting tumor cell survival during hypoxia. Accordingly, shRNA-knockdown of CALM1, CALU, and RCN1 expression reduced hypoxic tumor cell resistance to low-dose radiation and increased apoptosis. These data indicate that γ-irradiation of hypoxic tumor cells induces up-regulation of calcium-binding proteins that promote cancer cell survival and may limit the efficacy of radiotherapy in the clinic.